Revitalizing Academic Services: A Qualitative Investigation into Strategic Management Implementation - Yayah Huliatunisa; Diding Nurdin; Johar Permana (STAI Hubbulwathan Duri, 2023)
The purpose of this study is to analyze the quality of academic services at the Faculty of Health Sciences, through strategic management steps, including environmental analysis, formulation, implementation, evaluation of performance measurement, using descriptive qualitative methods. Data collection by qualitative interviews was carried out on five sources of information, qualitative observation, documentation study and literature study. Data were analyzed using open coding, axial coding and selected coding strategies. Triangulation was chosen as a technique to check the validity of research data. The results of the study show that in an effort to achieve its goals, the institution has not been able to reach the efficient stage, meaning that it really requires a lot of time, adequate costs needed, university support and leadership, loyalty and commitment of the entire academic community so that management functions run well, develop various resources. local wisdom-based funds, improvement and development of its resources.